The CanMEDS Competency Framework in laboratory medicine: A phenomenographic study exploring how professional roles are applied outside the clinical environment - Bogaty, Chloe; Frambach, Janneke (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Background: The CanMEDS Competency Framework is an internationally recognized model used to outline the proficiencies of a physician. It has predominantly been studied in clinical environments but not all medical specialties take part in direct patient contact. In laboratory medicine, the role of the physician is to promote and enhance patient diagnostics by managing and overseeing the functions of a diagnostic laboratory.Methods: This phenomenographic study explores the lived experiences of biochemistry, microbiology, and pathology residency program directors to better understand how they utilize the CanMEDS competencies. Eight laboratory medicine program directors from across Canada were individually interviewed using a semi-structured interview, and the data was analysed using inductive thematic analysis.Results: The findings show that the current framework is disconnected from the unique context of laboratory medicine with some competencies appearing unrelatable using the current standardized definitions and expectations. Nevertheless, participants considered the framework to be an appropriate blueprint of the competencies necessary for their professional environment, but to make it accessible more autonomy is required to adapt the framework to their needs.Conclusion: Newer renditions of the CanMEDS Competency Framework should better consider the realities of non-clinical disciplines.